Analisis Pengawasan Fasilitas Pada Terminal 2 Bandar Udara Internasional Juanda Surabaya - Dhaifina Kaila Haniifah; I Made Yudhistira Sulandra; Elfi Amir; Rany Adiliawijaya Putriekapuja (Jurnal Bisnis dan Operasi Penerbangan, 2026)
Airport Operation Landside and Terminal (AOLT) is an important unit in facility maintenance in accordance with SOP. This study aims to evaluate the performance of AOLT officers in overseeing the facilities in the departure waiting area of the terminal. The research uses a qualitative method with primary data from interviews and direct observations at Juanda International Airport Surabaya, and secondary data from facility supervision reports. Data analysis is conducted descriptively through data reduction, presentation, and conclusion drawing. The results show that AOLT officers’ patrol and inspection of terminal facilities are well executed, but some issues remain, such as errors in the Flight Information Display System (FIDS), non-functioning digital clocks at departure gates, and roof leaks in one of the tenants' areas in the waiting room. These issues are promptly addressed through coordination with AOCC, ATNOS, the Mechanical Section, and other relevant parties.